Understanding the impact of culture on business IT alignment within a South African parastatal - Carolissen, Lisle Kim (Department of Information Systems, 2019)
Business IT Alignment (BITA) remains a challenge for many organisations and is repeatedly ranked highly by Business and IT executives in an annual survey by the Society for Information Management (SIM). BITA has been defined as applying information technology (IT) in an appropriate and timely way, in harmony with business strategies, goals and needs. BITA maturity provides organisations with a way to determine the level of maturity of the BITA activities that is the management activities performed to attain a better alignment between IT function and the organisational goals. Mature alignment develops into a relationship where IT and other business functions adapt their strategies together. Previous research on BITA has focused more on formal structures such as reporting structures, decision-making rights and centralisation vs decentralisation, rather than informal structures such as relationship-based structures, including organisational culture, that go beyond the formal division of labour. The impact of culture on BITA has often been de-emphasised in earlier studies, leaving a gap in alignment research. Culture has been defined as a set of shared, taken-for-granted implicit assumptions that a group holds and determines how it perceives, thinks about and reacts to its various environments. Culture at an organisational however, has been defined as the culture within an organisation that includes the common expectations, goals, beliefs, ideas, common understanding and norms of the people in the organisation which varies between organisations. Culture at a group and organisational level have the same content and meaning and are theoretically isomorphic, meaning they both influence behaviour through shared, social normative cues. This study, conducted within a parastatal organisation, focused on culture at an organisational level. The purpose of this research was to explore and describe the organisational culture and BITA as indicated by the BITA maturity level within a South African parastatal, to compare perceptions of IT vs business groups with regards to BITA maturity, to explore and describe the relationships between cultural dimensions and BITA maturity criteria, and to determine whether the existing culture within a South African parastatal supports BITA. The research study adopted an interpretive philosophy in order to develop an understanding of the impact of culture on BITA within a South African parastatal. The research strategy was by means of a single case study. The study was qualitative in nature, data being collected by means of semi-structured interviews and company documents. The Competing Values Framework (CVF) formed the theoretical basis through which cultural types were identified deductively for each of the six cultural dimensions of the organisation. The Strategic Alignment Maturity Model was used to describe the BITA maturity criteria. The impact of culture on BITA maturity criteria was determined inductively. The study contributes theoretically through an explanation theory of how culture impacts BITA maturity positively and negatively through propositions of theory. In addition, it contributes practically suggesting that organisations wanting to improve their BITA must change their culture first. Practically, it serves as a guideline to managers and leaders within government organisations as to the cultural dimensions that are more likely to improve BITA such as 'success criteria and value’ and 'strategic emphasis’. Findings reveal incongruence in perceptions of the overall organisational culture within a South African parastatal for both Business and IT groups, with an overall dominant culture of Hierarchy. BITA maturity was negatively impacted by the cultural dimensions, Organisational leadership (Hierarchy) and Human Resource management (Clan/Hierarchy). In contrast, BITA was positively impacted by success criteria and value (Market) and strategic emphasis (Adhocracy). Overall, an incongruent culture seemed to negatively impact BITA maturity with a low overall BITA maturity level.